O mais completo dos sports espirituaes: o cinema silencioso em Barbacena (Minas Gerais, 1914-1931) - Igor Maciel da Silva (2021)
The studies that investigated the activities of cinema in Barbacena, Minas Gerais, at the beginning of the 20th century, paid special attention to the work of Paulo Benedetti: an Italian immigrant who opened the first cinematographic exhibition house in the city and developed a sound technique for some of the documentaries that he recorded in the region – this last activity being what is commonly highlighted by these narratives. In another direction, this thesis aims to write the history of silent cinema in Barbacena, with the general objective of mapping the activities of the cinematographic houses in Barbacena in the silent period, between 1914 and 1931. The specific objectives are: 1) to investigate the functioning of places that projected films, including the owners, days and times of cinematographic exhibitions, entrance fees, types of programming, supplier companies, regular audience, etc.; 2) recognize the meanings associated with cinema; 3) point out the other uses and sociability provided by film establishments. The methodology adopted is the documentary analysis built from the assessment of printed documents, especially copies of newspapers, magazines, almanac, yearbook and memoirists' books, with ―Cidade de Barbacena‖ newspaper as the main source due to its importance in the city and the number of editions available on file. The narrative also features images that are specially disposed in an illustrative way. The text is organized as follows: Introduction – presents the fundamental idea of the thesis and consists of an investigation of research identified on cinema in Barbacena, as well as a justification for the investigation; Various aspects of Barbacena – generally describes the activities of the city in the period considered, including its economic, industrial, architectural and identified entertainment development; Cinema in Barbacena – initially contains a balance of the dynamics of the activities of the identified projector houses, which includes: number of establishments, managers, organization of operation, forms of admission, types of programming, regular audience, their forms of use and expectations, programs offered to the assistants, marks of the films projected and the themes highlighted. Then, details of each cinema are checked in sections.